Contrasting effects of nitric oxide and corticotropin- releasing factor within the dorsal periaqueductal gray on defensive behavior and nociception in mice - Miguel, T.T. [UNESP]; Gomes, K.S. [UNESP]; Nunes-de-Souza, R.L. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2012)
The anxiogenic and antinociceptive effects produced by glutamate N-methyl-D-aspartate receptor activation within the dorsal periaqueductal gray (dPAG) matter have been related to nitric oxide (NO) production, since injection of NO synthase (NOS) inhibitors reverses these effects. dPAG corticotropin-releasing factor receptor (CRFr) activation also induces anxiety-like behavior and antinociception, which, in turn, are selectively blocked by local infusion of the CRF type 1 receptor (CRFr1) antagonist, NBI 27914 [5-chloro-4-(N-(cyclopropyl)methyl-N-propylamino)-2-methyl-6-(2,4,6-trichlorophenyl)aminopyridine]. Here, we determined whether i) the blockade of the dPAG by CRFr1 attenuates the anxiogenic/antinociceptive effects induced by local infusion of the NO donor, NOC-9 [6-(2-hydroxy-1-methyl-2-nitrosohydrazino)-N-methyl-1-hexanamine], and ii) the anxiogenic/antinociceptive effects induced by intra-dPAG CRF are prevented by local infusion of Nω-propyl-L-arginine (NPLA), a neuronal NOS inhibitor, in mice. Male Swiss mice (12 weeks old, 25-35 g, N = 8-14/group) were stereotaxically implanted with a 7-mm cannula aimed at the dPAG. Intra-dPAG NOC-9 (75 nmol) produced defensive-like behavior (jumping and running) and antinociception (assessed by the formalin test). Both effects were reversed by prior local infusion of NBI 27914 (2 nmol). Conversely, intra-dPAG NPLA (0.4 nmol) did not modify the anxiogenic/antinociceptive effects of CRF (150 pmol). These results suggest that CRFr1 plays an important role in the defensive behavior and antinociception produced by NO within the dPAG. In contrast, the anxiogenic and antinociceptive effects produced by intra-dPAG CRF are not related to NO synthesis in this limbic midbrain structure.
Keywords: Nitric oxide; Corticotropin-releasing factor; Periaqueductal gray; Defensive behavior; Antinociception; Mice